Criminal Liability for Online Gender-Based Sextortion Against Women Under Indonesian Criminal Law - Rafli H. Husain; Dian Ekawaty Ismail; Mohamad Rivaldi Moha (Yayasan Cerdas Pedia Indonesia, 2026)
The development of digital technology has prompted an increase in Online Gender-Based Violence (OGBV) cases, particularly in the form of sextortion targeting women, which has not been specifically regulated under Indonesian criminal law. This study aims to analyze the criminal liability of sextortion perpetrators under Indonesian criminal law, using normative legal research methods with statutory and conceptual approaches. The findings indicate that the handling of sextortion in Indonesia remains fragmented across multiple regulations, namely the Criminal Code, the Electronic Information and Transactions Law, the Pornography Law, and the Sexual Violence Crimes Law. This regulatory fragmentation creates legal uncertainty, judicial inconsistency, and suboptimal protection for victims. Therefore, a specific sextortion criminal provision with a gender perspective is urgently needed to ensure legal certainty and substantive justice for female victims in the digital era.